Effects of in vivo applications of peripheral blood‐derived mesenchymal stromal cells (PB‐MSCs) and platlet‐rich plasma (PRP) on experimentally injured deep digital flexor tendons of sheep1. Issue 2 (14th August 2012) - Martinello, Tiziana; Bronzini, Ilaria; Perazzi, Anna; Testoni, Stefania; De Benedictis, Gulia Maria; Negro, Alessandro; Caporale, Giovanni; Mascarello, Francesco; Iacopetti, Ilaria; Patruno, Marco
Abstract Tendon injuries, degenerative tendinopathies, and overuse tendinitis are common in races horses. Novel therapies aim to restore tendon functionality by means of cell‐based therapy, growth factor delivery, and tissue engineering approaches. This study examined the use of autologous mesenchymal stromal cells derived from peripheral blood (PB‐MSCs), platelet‐rich plasma (PRP) and a combination of both for ameliorating experimental lesions on deep digital flexor tendons (DDFT) of Bergamasca sheep. In particular, testing the combination of blood‐derived MSCs and PRP in an experimental animal model represents one of the few studies exploring a putative synergistic action of these treatments. Effectiveness of treatments was evaluated at 30 and 120 days comparing clinical, ultrasonographic, and histological features together with immunohistochemical expression of collagen types 1 and 3, and cartilage oligomeric matrix protein (COMP). Significant differences were found between treated groups and their corresponding controls (placebo) regarding tendon morphology and extracellular matrix (ECM) composition. However, our results indicate that the combined use of PRP and MSCs did not produce an additive or synergistic regenerative response and highlighted the predominant effect of MSCs on tendon healing, enhanced tissue remodeling and improved structural organization. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 306–314, 2013